ARABIC ETHNIC SOCIAL LIFE IN PAMBUSUANG VILLAGE, BALANIPA DISTRICT, POLEWALI MANDAR REGENCY - Hafsah; Ahmad M. Sewang; Syamzan Syukur (International Journal of Islamic Studies, 2022)
This study examines the social life of Arabic ethnic in Pambusuang village, Balanipa sub-district, Polewali Mandar district. This study aims to analyze and describe the influence of Arabic ethnic in Pambusuang. This study is qualitative field research using historical, sociological, cultural anthropological, and political approaches. This study carried out the heuristic steps or data collection by conducting observation, interviews, and documentation. After the data is obtained, the researcher undertook the source criticism, interpretation, and the stages of doing historiography. The results of this study found that: 1) The arrival of Arabic ethnic who settled in Pambusuang went through three stages. The first stage was in the seventeenth century, marked by the arrival of Sheikh Al-Adiy, the arrival of Sayyid Bollo marked the second stage, and the third stage was marked by the arrival of Sayyid Alwi bin Sahl Jamallahil. 2) The Arabic ethnicity banned the marriage between Sharifah and Ahwal. They assimilated with the local communities and tried to connect with rabitha Awaliyah so they could be able to detect any members of a non-sayyid group but claimed themselves as a sayyid, and 3) During the period as a part of Pambusuang society, Arabic ethnic had given much influence in the fields of da’wah, education, and politics.